**Coded Data Proofs (4):**

Say that: y=x/k + C

And that: x={p, q} and y={p/k+C, q/k+C}

If this is the case:

And also:

Therefore, you’d have to say that:

**Coded Data Proofs (4):**

Say that: y=x/k + C

And that: x={p, q} and y={p/k+C, q/k+C}

If this is the case:

And also:

Therefore, you’d have to say that:

**Coded Data Proofs (3):**

Say y=kx+C and also that:

x={p, q} and y={kp+C, kq+C}

This would mean that:

And if the above is true:

Therefore:

**Coded Data Poofs (2):**

Say y=x/k and that: x={p, q}, y={p/k, q/k}.

This would mean that:

It would also mean that:

And if the above is true:

**Coded Data Proofs (1):**

Say y=kx, and also that: x={p, q}, y={kp, kq}.

This would mean that:

Therefore, when y=kx:

What we’d also be able to conclude is that:

When considering the above, we can deduce that:

Therefore, when y=kx:

Prove that if set A, of size , has mean and set B, of size , has a mean then the **mean of the combined** set of A and B is .

——————

Set A:

Therefore:

Therefore:

——————

Set B:

Therefore:

Therefore:

So: